Identifying and Prioritizing Factors Affecting Patient\'s Length of Stay in Selected Hospitals Affiliated to Tehran and Iran University of Medical Sciences - Saeid Mahmoudi; Zeinab Gholampour Noghondar; Farhad Habibi Nodeh; Hossein Safari; Parvin Abbasi Borogeni (Tehran University of Medical Sciences, 2018)
Background: Length of stay is one of the most important and practical indices used in hospitals today which represents the performance and efficiency of the hospitals. This study aimed to identify the factors affecting length of stay in hospitals affiliated to Tehran and Iran Universities of Medical Sciences based on Hierarchical Analysis Technique. Materials and Methods: This descriptive cross-sectional study was conducted in 2013. Study population consisted of 40 participants using purposive sampling method in the two groups including 13 matrons (nursing managers) and 27 supervisors (Clinical and educational) of hospitals affiliated to Tehran and Iran Universities of Medical Sciences. Data collection tool was the paired comparisons questionnaire which was confirmed validity by experts using Lawshe and reliability by Inconsistency Ratio. Data analysis was performed using Expert Choice software version 11. Results: In general, in the studied hospitals, study results revealed that the "diagnostic, treatment and care methods (treatment efficacy)" with the mean of 21.4% and "admission and discharge in the end days of the week and the days off" with an average of 0.36 were the highest and the lowest priority is given to other factors affecting the length of stay of the patient,respectively. Conclusion: Efficacy of provided treatment through using equipment, appropriate diagnostic and therapeutic procedures and factors related to hospital manpower were effective on length of stay in quantitative and qualitative dimensions. These important issues need more planning and pay attention by hospital officials.